Global trends in countries' perceptions of the Belt and Road Initiative - Alicia García Herrero; Robin Schindowski (Bruegel, 2023)
Drawing on global media reports, we conduct a sentiment analysis of the image of China's Belt and Road Initiative (BRI) and the evolution of its image over time. Our main finding is that perceptions of the initiative deteriorated significantly in many geographies from 2017 to 2022. The notable exception is in sub-Saharan Africa where the BRI's image remains positive, even if slightly less so than in the past. This is notwithstanding increases in debt levels with China, much of which now face potential restructuring. Furthermore, we find significant inter- and intra-regional differences in the average sentiment towards China's landmark project, as well as a much worse image of the initiative in countries which, until today, are not part of the BRI. Finally, we focus on the European Union, Africa and China's immediate neighbourhood to better understand the complexities behind the perceived benefits and challenges associated with China's Belt and Road Initiative.
Keywords: 330; EU-China relations; geopolitics